Withdrawing attempt and its related factors among Iranian substance users: a case-control study - Gholamhossein Shahraki; Zahra Sedaghat; Mohammad Fararouei (BMC, 2018)
Abstract Background Substance dependence is considered as an important health disorder with a wide and serious range of psychosocial effects. With regard to the large number of people with substance dependency in Iran and high failure rate of quitting attempts, the aim of this study was to identify contributing factors to quitting substance dependency among patients in Yasuj the capital of Kohgilooyeh and Boyerahmad province. Methods This case-control study was conducted on 150 current substance users (as control group) and 187 patients who voluntarily introduced themselves to governmental and private residential treatment camps (as case group). The participants in the case group were selected via two stage cluster sampling among those admitted to residential treatment camps. Those in the control group were selected via snowball sampling among current substance users. Results Based on the results from multiple logistic regression analysis, significant associations were observed between attempting to withdraw substance use and father's education (OR high school or university /illiterate = 0.36, 95%CI: 0.18 to 0.72, P = 0.004) and smoking (OR yes/no = 4.26, 95%CI = 1.90 to 9.57, P < 0.001) were identified. Conclusions This study introduced father's education as an obstacle to attempting to quit substance dependency. This finding can be justified by easier access to money and therefore less financial pressure in providing drugs among those with wealthier families. Also, smoking was more common among those who registered with the camps. This is possibly due to the quitters attempt to replace the drugs with cigar smoking as an alternative. Training families in helping their members in preventing or quitting substance dependency is a potentially useful approach. Studies are needed to define whether the common belief that smoking helps in withdrawing substance use is helpful.